Room-temperature exceptional-point-driven polariton lasing from perovskite metasurface - Masharin, M. A. (2023)
Excitons in lead bromide perovskites exhibit high binding energy and high oscillator strength, allowing for a strong light-matter coupling regime in the perovskite-based cavities localizing photons at the nanoscale. This opens up the way for the realization of exciton-polariton Bose-Einstein condensation and polariton lasing at room temperature -- the inversion-free low-threshold stimulated emission. However, polariton lasing in perovskite planar photon cavities without Bragg mirrors has not yet been observed and proved experimentally. In this work, we employ perovskite metasurface, fabricated with nanoimprint lithography, supporting so-called exceptional points to demonstrate the room-temperature polariton lasing. The exceptional points in exciton-polariton dispersion of the metasurface appear upon optically pumping in the nonlinear regime in the spectral vicinity of a symmetry-protected bound state in the continuum providing high mode confinement with the enhanced local density of states beneficial for polariton condensation. The observed lasing emission possesses high directivity with a divergence angle of around 1degrees over one axis. The employed nanoimprinting approach for solution-processable large-scale polariton lasers is compatible with various planar photonic platforms suitable for on-chip integration.